Profile of gut microbiota in patients with traumatic thoracic spinal cord injury and its clinical implications: a case-control study in a rehabilitation setting. Issue 1 (1st January 2021) - Yu, Binbin; Qiu, Huaide; Cheng, Shupeng; Ye, Feng; Li, Jiahui; Chen, Sijing; Zhou, Li; Yang, Yumei; Zhong, Caiyun; Li, Jianan
ABSTRACT: Gut microbiota are the candidate biomarkers for neurogenic bowel dysfunction (NBD) in patients with spinal cord injury (SCI). We aimed to identify the common features between patients with varying degree of thoracic SCI and healthy individuals and subpopulations of microbiota correlated with the serum biomarkers. Twenty-one patients with complete thoracic SCI (CTSCI), 24 with incomplete thoracic SCI (ITSCI), and 24 healthy individuals (HC) were enrolled in this study. Fresh stool samples and clinical data were collected from all participants, and their bowel functions with SCI were assessed. Microbial diversity and composition were analyzed by sequencing the 16S rRNA gene. The features of gut microbiota correlated with the serum biomarkers and their functions were investigated. The mean NBD score of patients with CTSCI was higher than that of patients with ITSCI. Diversity of the gut microbiota in SCI group was reduced, and with an increase in the degree of damage, alpha diversity had decreased gradually. The composition of gut microbiota in patients with SCI was distinct from that in healthy individuals, and CTSCI group exhibited further deviation than ITSCI group compared to healthy individuals. Four serum biomarkers were found to be correlated with most differential genera. Patients with thoracic SCI present gut dysbiosis, which is more pronounced in patients with CTSCI than in those with ITSCI. Therefore, the gut microbiota profile may serve as the signatures for bowel and motor functions in patients with thoracic SCI. GRAPHICAL ABSTRACT: uf0001